2022
DOI: 10.3390/ma15238612
|View full text |Cite
|
Sign up to set email alerts
|

N+-Implantation on Nb Coating as Protective Layer for Metal Bipolar Plate in PEMFCs and Their Electrochemical Characteristics

Abstract: Nitrogen ions were implanted into the coated Nb layer by plasma immersion ion implantation to improve resistance to corrosion of a metal bipolar plate. Due to nitrogen implantation, the corrosion behavior of the Nb layer was enhanced. The electron microscope observation reveals that the microstructure of the Nb layer became denser and had fewer defects with increasing implantation energy. As a result, the densified structure effectively prevented direct contact with the corrosive electrolyte. In addition, at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Surface engineering and coating technologies have been used to protect the surface of bipolar plates. In the work reported in [ 11 ], Kim et al deposited a Nb coating on stainless steel, followed by N + ion implantation. The authors studied the composition, structure and corrosion performance of the duplex-treated material and found that N+ implantation effectively modified the deposited Nb coating to form an improved protective film with much enhanced corrosion resistance for the metal bipolar plate.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Surface engineering and coating technologies have been used to protect the surface of bipolar plates. In the work reported in [ 11 ], Kim et al deposited a Nb coating on stainless steel, followed by N + ion implantation. The authors studied the composition, structure and corrosion performance of the duplex-treated material and found that N+ implantation effectively modified the deposited Nb coating to form an improved protective film with much enhanced corrosion resistance for the metal bipolar plate.…”
mentioning
confidence: 99%
“…The authors studied the composition, structure and corrosion performance of the duplex-treated material and found that N+ implantation effectively modified the deposited Nb coating to form an improved protective film with much enhanced corrosion resistance for the metal bipolar plate. This work provides new possibilities for surface modification to improve fuel cell performance and for other applications [ 11 ].…”
mentioning
confidence: 99%